Central role of PKCα in isoenzyme-selective regulation of cardiac transient outward current Ito and Kv4.3 channels - Scholz, Eberhard P.; Welke, Florian; Joß, Nadja Janina; Seyler, Claudia; Zhang, Wei; Scherer, Daniel; Völkers, Mirko; Bloehs, Ramona; Thomas, Dierk; Katus, Hugo; Karle, Christoph; Zitron, Edgar (Journal of molecular and cellular cardiology, 2011)
The transient outward current Ito is an important determinant of the early repolarization phase. Ito and its molecular basis Kv4.3 are regulated by adrenergic pathways including protein kinase C. However, the exact regulatory mechanisms have not been analyzed yet. We here analyzed isoenzyme specific regulation of Kv4.3 and Ito by PKC. Kv4.3 channels were expressed in Xenopus oocytes and currents were measured with double electrode voltage clamp technique. Patch clamp experiments were performed in isolated rat cardiomyocytes. Unspecific PKC stimulation with PMA resulted in a reduction of Kv4.3 current. Similar effects could be observed after activation of conventional PKC isoforms by TMX. Both effects were reversible by pharmacological inhibition of the conventional PKC isoenzymes (Gö6976). In contrast, activation of the novel PKC isoforms (ingenol) did not significantly affect Kv4.3 current. Whereas TMX-induced PKC activation was not attenuated inhibition of PKCβ, inhibition of PKCα with HBDDE prevented inhibitory effects of both PMA and TMX. Accordingly, stimulatory effects of PMA and TMX could be mimicked by the α-isoenzyme selective PKC activator iripallidal. Further evidence for the central role of PKCα was provided with the use of siRNAs. We found that PKCα siRNA but not PKCβ siRNA abolished the TMX induced effect. In isolated rat cardiomyocytes, PMA dependent Ito reduction could be completely abolished by pharmacologic inhibition of PKCα. In summary we show that PKCα plays a central role in protein kinase C dependent regulation of Kv4.3 current and native Ito. These results add to the current understanding of isoenzyme selective ion channel regulation by protein kinases.
Gesehen am 25.10.2022